(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
Consider (M, g) as an n-dimensional compact Riemannian manifold. Our main aim in this paper is to study the first eigenvalue of (p, q)-Laplacian system on C-totally real submanifold in Sasakian space of form M^2m+1 (κ). Also in the case of p, q > n we show that for λ_1,p,q arbitrary large there exists a Riemannian metric of volume one conformal to the standard metric of S^n.